Medication Safety in Municipal Health and Care Services - Sletvold, Hege (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Medicines constitute an essential part of healthcare delivery and help to prevent or treat illness, influence quality of life, and generally increase life expectancy. However, medications can also cause harm if prescribed irrationally, dispensed or used incorrectly, and monitored or followed up insufficiently. In this anthology, we showcase the challenges of medication management and the rational use of medicines in municipal health and care services, and present various strategies and measures related to medication safety. The contributors are researchers representing a wide range of disciplines, with experience from different levels of healthcare services and different areas within the research and education sectors. We hope to raise awareness, engage and enable discussion of initiatives and strategies to improve patient safety related to medications in municipal health and care services, and create a basis for further research to promote safe medication management and rational use of medicines. This anthology will be of interest to anyone involved in or concerned with medication safety, primarily healthcare professionals, academic staff, researchers, policymakers, and managers in healthcare services.